Efforts of Islamic Religious Education Teachers in Improving Learning Outcomes in Aqidah Subjects of Grade VII Morals in MTs Al Furqon Klari Karawang - Ilyas Prasetyo; Ajat Rukajat; Sutarjo Sutarjo (Universitas Bengkulu, 2021)
This Akhlak Creed subject is a branch of Islamic religious education, the subject of moral faith in forming religious character emphasizes the aspect of habituation early on and not only the responsibility of the school but all participate in improving the learning outcomes of learners involving families, schools and community environments. The purpose of this study is to find out the efforts of PAI teachers in improving the learning outcomes of learners in moral faith subjects carried out in class VII at MTs Al-Furqon Klari Karawang. The subjects of the study were principals, PAI teachers and students. This research method is qualitatively descriptive i.e. written or oral of the research object. Data collection techniques use observations, interviews, and documentation. The result of PAI teacher efforts, learners in moral faith subjects there is an increase in terms of written value and skills.